2017
DOI: 10.1111/jcpt.12587
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific polymerase chain reaction for the detection of single nucleotide polymorphism in amlodipine-induced gingival enlargement

Abstract: Drug-induced complications can potentially be a result of genetic factors, in combination with various local and systemic factors. Identifying genetic polymorphisms early might help predict adverse reactions and determine prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…In AS-PCR, Taq polymerase can effectively carry out DNA synthesis reactions only when the base at the 3′ end of the primer is correctly matched with the template DNA [ 61 , 69 ]. The primers were designed based on the SNP of TraesCS7B01G164000 detected in wheat L658 and L958, as shown in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…In AS-PCR, Taq polymerase can effectively carry out DNA synthesis reactions only when the base at the 3′ end of the primer is correctly matched with the template DNA [ 61 , 69 ]. The primers were designed based on the SNP of TraesCS7B01G164000 detected in wheat L658 and L958, as shown in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…Clínicamente, se observa un crecimiento anormal de la encía, en casos muy graves puede llegar a cubrir todas las piezas dentales, en casos menores se observa papilas interdentales en forma de una superficie lobulada y fibrótica de color rosado. Los fármacos antihipertensivos relacionados son: los bloqueadores de los canales de calcio y calcio antagonista (J et al, 2021;Kala et al, 2018;Kose et al, 2020;Lauritano et al, 2019;Vidal et al, 2018)…”
Section: Hiperplasia Gingivalunclassified
“…The incidence of periodontitis in China as a whole is about 70%-85%. Periodontitis is a disease that endangers human oral health, and there is also a certain degree of correlation with the occurrence of hypertension [3]. Related studies have shown that periodontitis is related to the prevalence of hypertension, and the occurrence of hypertension will also cause the risk and severity of periodontitis.…”
Section: Introductionmentioning
confidence: 99%